Volume–outcome relation for contemporary percutaneous coronary interventions (PCI) in daily clinical practice: is it limited to high-risk patients? Results from the Registry of Percutaneous Coronary Interventions of the Arbeitsgemeinschaft Leitende Kardiologische Krankenhausärzte (ALKK). Issue 3 (30th July 2007) - Zahn, R; Gottwik, M; Hochadel, M; Senges, J; Zeymer, U; Vogt, A; Meinertz, T; Dietz, R; Hauptmann, K E; Grube, E; Kerber, S; Sechtem, U
Abstract : Objective: The formerly observed volume–outcome relation for percutaneous coronary interventions (PCIs) has recently been questioned. Design: We analysed data of the PCI registry of the Arbeitsgemeinschaft Leitende Kardiologische Krankenhausärzte. Patients: In 2003 a total of 27 965 patients at 67 hospitals were included. Results: The median PCI volume per hospital was 327. In-hospital mortality was 1.85% in hospitals belonging to the lowest PCI volume quartile and 1.21% in the highest quartile (p for trend <0.001). Two groups of patients were then compared according to their treatment at hospitals with either <325 PCIs (n = 5754) or >325 PCIs (n = 22 211) per year. Logistic regression analysis showed that a PCI performed at hospitals with a volume of >325 PCI/year was independently associated with a lower hospital mortality (OR = 0.67, 95% CI: 0.52 to 0.87; p = 0.002). If PCI was performed in patients with acute myocardial infarction there was a significant decline in mortality with increasing volume (p for trend = 0.004); however, there was no association in patients without a myocardial infarction. Conclusions: This analysis of contemporary PCI in clinical practice shows a small but significant volume–outcome relation for in-hospital mortality. However, this relation was only apparent in high-risk subgroups, such as patients presenting with acute myocardial infarction.